Peripheral Nerve Ultrasound for the Differentiation between ALS, Inflammatory, and Hereditary Polyneuropathies - Annkatrin Hildebrand; Frank Schreiber; Luisa Weber; Philipp Arndt; Cornelia Garz; Susanne Petri; Johannes Prudlo; Sven G. Meuth; Yannic Waerzeggers; Solveig Henneicke; Stefan Vielhaber; Stefanie Schreiber (Medicina, 2023)
Background and Objectives: Ultrasound (US) is a non-invasive tool for the in vivo detection of peripheral nerve alterations. Materials and Methods: In this study, we applied nerve US to assist the discrimination between the spectrum of amyotrophic lateral sclerosis (ALS, n = 11), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP, n = 5), and genetically confirmed Charcot–Marie–Tooth disease (CMT, n = 5). All participants and n = 15 controls without neurological diseases underwent high-resolution US of the bilateral tibial nerve. The nerve cross-sectional area (CSA) and nerve microvascular blood flow were compared between the groups and related to cerebrospinal fluid (CSF) measures, clinical symptoms, and nerve conduction studies. The analyses are part of a larger multimodal study on the comparison between US and 7 Tesla (7T) magnetic resonance neurography (MRN). Results: The patients and controls were matched with respect to their demographical data. CMT had the longest disease duration, followed by CIDP and ALS. CSA was related to age, weight, and disease duration. CSA was larger in CMT and CIDP compared to ALS and controls. The blood flow was greatest in CIDP, and higher than in CMT, ALS, and controls. In ALS, greater CSA was correlated with greater CSF total protein and higher albumin quotient. The US measures did not correlate with clinical scores or nerve conduction studies in any of the subgroups. Conclusion: Our results point towards the feasibility of CSA and blood flow to discriminate between ALS, CIDP, and CMT, even in groups of small sample size. In ALS, larger CSA could indicate an inflammatory disease subtype characterized by reduced blood–nerve barrier integrity. Our upcoming analysis will focus on the additive value of 7T MRN in combination with US to disentangle the spectrum between more inflammatory or more degenerative disease variants among the disease groups.